Promoting Meaningful Learning Through the Use of Concept Maps - (:unkn) unknown (My University, 2018)
Background and significance: There have been dramatic changes in the healthcare system with the high use of technology. The healthcare needs of patients have increased due to the chronic diseases, and an increase in the number of the older population. These changes require nurses with high levels of thinking, knowledge and skills. It is vital to reconsider the teaching and learning methods used in nursing schools to ensure graduating nurses are capable of working in these challenging environments. The purpose of this naturalistic inquiry descriptive study is to explore the experiences and perspectives of undergraduate and graduate nursing students and faculty on the use of concept maps as a learning tool by students, and as a teaching and assessment tool by faculty at a nursing college in a public university, Jeddah, Saudi Arabia. At this stage, meaningful learning is defined as the ability of students to make sense of the content learned in-class, and their ability to recall the information during their exams. Methodology: Undergraduate and graduate nursing students were trained on the creation of concept maps. Faculty were trained on the use of concept maps as a teaching and assessment tool. Using convenient sampling method, the sample included 18 undergraduate students, 4 graduate students, and 4 faculty. Data was collected using focus groups with students and indepth individual interviews with faculty. Data was analyzed using thematic analysis. Findings:Three themes were identified; enablers, constraints and guidance and support. Conclusion: The results help faculty learn more about nursing students and understand their learning needs which will influence the faculty’s choice of teaching methods when planning for their courses and lessons. The results need to be complemented by empirical evidence on the use of concept maps by Saudi Arabian nursing students and faculty.
Keywords: Concept map; Faculty; Meaningful learning; Saudi Arabia; Students